Etnofarmakologi dan Potensi Bioaktivitas Daun dan Buah Sirsak (Annona Muricata): Artikel Review - Eka Nurul Qomaliyah (Department of Pharmacy, Bumigora University, 2022)
The leaves and fruit of soursop or Annona muracita have been used extensively as medicinal plants by people in various ethnic groups in Indonesia. Soursop leaves and fruit are believed to prevent and treat diabetes, obesity, and hypertension. Various scientific studies have proven the potential activity of soursop leaves and fruit to have antidiabetic, antioxidant, antiobesity, cytotoxic, anticancer, antihypertensive, antibacterial, anti-inflammatory, antirheumatic, and hepatoprotective effects. Based on literature studies related to phytochemicals sourced from Scopus, Science direct, PubMed, ProQuest reports that at least 54 secondary metabolites have been isolated and identified. These compounds include a group of alkaloids, phenols, and acetogenins. This article presents a brief overview that seeks to compile all information regarding the phytochemistry, ethnopharmacology, and bioactivity of soursop leaves and fruit.